The definite article with proper names in Ancient Greek: a study in Herodotus and Thucydides - Firmino, Luís Alberto Goulart (2024)
Proper names in Ancient Greek may appear with or without the definite article. This dissertation investigates what are the contexts in which we find one case or the other. To do so, a theoretical framework of Semantics and Pragmatics of proper names and definite articles was adopted. Proper names are rigid designators (Kripke 1981), nominal expressions that denote a particular individual as their referent without describing such individual. Definite articles are grammatical expressions that assert the existence and uniqueness of a noun\'s referent; pragmatically, they also implicate the identifiability of such referent. Given that proper names refer directly to an individual – existing and unique – the function of the definite article with them is related more closely to the identifiability of such referents. Furthermore, the theoretical framework was modulated by typological studies about the use of the definite article with proper names, which show that there are different variables, from several language levels, that may affect the use of the definite article with proper names. Consequently, besides the matter of referents\' identifiability, other contexts were tested as to their correlation with the use of the definite article with proper names in Classical Greek. The corpus adopted for this study was composed of five names from Herodotus\' Histories and five other names from Thucydides\' History of the Peloponnesian War. As a result, the contexts where proper names tend to not have the definite article in both authors are: the first position of a referential chain; when accompanied by appositive constructions; when in the genitive case; and when in direct discourse. Conversely, the contexts in which proper names tend to have the definite article in both authors are: when the name is the subject of a transitive verb, or else is the express agent of a passive verb; when the name is the subject of a speech verb; when there is a \"cluster\" of definite articles. Many of these tendencies correspond more or less strictly to the notion that the definite article is related to the identifiability of proper names\' referents